KEBUTUHAN TENAGA PELAPORAN DENGAN METODE ANALISIS BEBAN KERJA PADA MASA PANDEMI COVID-19 DI RSU “X” - Widia Nurrul Irsani; Sali Setiatin; Aris Susanto (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
Reporting personnel are one of the important human resources to determine the performance of the medical record work unit. Determining the right number of human resources must be based on systematic calculations, one method that can be used is the workload analysis method. The Covid-19 pandemic period requires health service facilities including hospitals to report related to Covid-19 events, which has increased the workload of medical recorders in the reporting section. At the General Hospital "X" there are 32 types of reports, including 5 additional types of reports during the Covid-19 pandemic that must be carried out in the context of implementing the handling of the Covid-19 pandemic. The number of reporting personnel in the medical record unit of the General Hospital "X" currently available is 3 people. This study aims to review the need for reporting personnel for the medical record work unit at the "X" General Hospital with the workload analysis method during the Covid-19 pandemic. The research method used is a qualitative method with a descriptive approach. The data collection techniques used are observation, interviews, and literature review that are relevant to the research. From the research conducted, a problem was found, there was the incompatibility of the number of reporting personnel based on the results of calculations using the workload analysis method. According to calculations, there should be 4 reporting personnel, while the currently available reporting personnel are 3 people. The suggestion given to overcome these problem is to adjust the number of reporting personnel by adding 1 reporting person.